Physicochemical Properties of Human Hair using Fourier Transform Infra-Red (FTIR) and Scanning Electron Microscope (SEM) - Obinna, Ezenwali Moses (ASEAN Journal for Science and Engineering in Materials, 2022)
This research work is to investigate the physicochemical properties of human hair. Data was obtained by analyzing human hair using Fourier Transform Infra-Red and Scanning Electron Microscope. Several results were obtained, including data on the chemical properties of human hair.